Nanoporous graphene – novel material for production of semipermeable membranes - Konieczny, Krystyna; Bodzek , Michał (Instal, 2019)
In recent decades, novel and promising materials (e.g. carbon nanotubes, nanoporous graphene and graphene oxide) suitable to be used in manufacturing of high-capacity membranes for water desalination and water and wastewater treatment have been developed. Membranes made of these materials enable to obtain significantly higher water/permeate fluxes than currently used thin film composite polyamide membranes. In this paper methods of synthesis of membranes containing graphene and its derivatives, their properties and application areas have been discussed. Chemical and physical functions of graphene and graphene oxide influencing water desalination efficiency and antifouling properties were also described. Additionally, methods of functionalization and techniques of graphene and graphene-derivatives processing enhancing membranes’ active layer stability, retention of salts, water flux, ions transport mechanism and fouling decrease, are also presented.